1991
DOI: 10.1126/science.252.5009.1177
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Synchronization of Oscillatory Neuronal Responses in Cat Visual Cortex

Abstract: Neurons in area 17 of cat visual cortex display oscillatory responses that can synchronize across spatially separate columns in a stimulus-specific way. Response synchronization has now been shown to occur also between neurons in area 17 of the right and left cerebral hemispheres. This synchronization was abolished by section of the corpus callosum. Thus, the response synchronization is mediated by corticocortical connections. These data are compatible with the hypothesis that temporal synchrony of neuronal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
462
3
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 865 publications
(500 citation statements)
references
References 11 publications
25
462
3
4
Order By: Relevance
“…These workers suggest, on the basis of observed loss of interhemispheric synchrony after cutting the corpus callosum, that longrange synchrony is mediated by axonal conduction between the synchronous areas of cortex (Engel et al, 1991a(Engel et al, ,b, 2001). Simulations have found that zero-lag synchrony can be established by this means provided the axonal conduction time between the synchronous regions of cortex does not exceed one third of the cycle time of the oscillation (König and Schillen, 1991).…”
Section: Possible Mechanisms Of Generation Of Global Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…These workers suggest, on the basis of observed loss of interhemispheric synchrony after cutting the corpus callosum, that longrange synchrony is mediated by axonal conduction between the synchronous areas of cortex (Engel et al, 1991a(Engel et al, ,b, 2001). Simulations have found that zero-lag synchrony can be established by this means provided the axonal conduction time between the synchronous regions of cortex does not exceed one third of the cycle time of the oscillation (König and Schillen, 1991).…”
Section: Possible Mechanisms Of Generation Of Global Synchronymentioning
confidence: 99%
“…Most authors have concentrated on a single frequency band, usually gamma. For example, early work using multiunit recording in cat visual cortex (Engel et al, 1991a) demonstrated the existence of interhemispheric synchronization in the gamma range. This suggested the influential hypothesis that synchrony of firing between widely separated areas of cortex may be the answer to the binding problem, producing ''dynamic representation of objects by assemblies of synchronously oscillating cells" (Engel et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma oscillations are a characteristic feature of network activity in 'desynchronized' cortical areas involved in processing of incoming sensory information in the awake state or during REM sleep (Singer and Gray, 1995;Maloney et al, 1997). Gamma oscillations have also been observed in vivo in the hippocampus and the entorhinal cortex of rats (Stumpf, 1965;Buzsáki et al, 1983;Chrobak and Buzsáki, 1998a;Bragin et al, 1995a), the amygdala, the entorhinal and perirhinal cortices and the neocortex of cats (Boeijinga and Lopes da Silva, 1988;Gray et al, 1989;Engel et al, 1991;Collins et al, 2001), the neocortex of the monkeys (Kreiter and Singer, 1996) and in the human neocortex (Llinás and Ribary, 1993;Uchida et al, 2001). Gamma oscillations are also induced by various pharmacological manipulations in vitro Buhl et al, 1998;Fisahn et al, 1998).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…The cells that are synchronized can be quite distant from one another (even in different hemispheres 58 ), and there is no other documentation of long-range synchronous activity 59 .…”
Section: Time and Bindingmentioning
confidence: 99%